Relationship between progesterone level on the day of human chorionic gonadotropin administration with outcomes of intra-cytoplasmic sperm injection in infertile couples - Mahsomeh Hajishafiha; Zahra Shahbazi; AbdolGhader Pakniyat; Sima Oshnouei; Nazila Kiarang (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Gonadotropin-releasing hormone agonists or antagonists are used in assisted reproductive technique cycles as premature luteinizing hormone secretion inhibition. Studies have been reported different and contradictory results on the serum progesterone effect on intra-cytoplasmic sperm injection. Objective: The purpose of this study was to evaluate the effect of serum progesterone level on the day of Human chorionic gonadotropin (HCG) administration on the intra-cytoplasmic sperm injection (ICSI) outcome in infertile women. Materials and Methods: 249 infertile couples candidated for ICSI were enrolled in the study. Their serum progesterone level on the day of HCG administration was measured and according to serum level, patients were divided into four groups of less than 0.9, 0.9-1.4, 1.5-1.9, and ≥2 ng/mL. The four groups were compared with each other regarding fertility outcomes. Results: Pregnancy rate was not significantly different among the four groups (p>0.05). Also, there was no significant difference among the groups regarding frequency of abortion and ectopic pregnancy. Conclusion: Serum progesterone level on the day of HCG administration does not have any significant effect on pregnancy outcomes, including abortion, ectopic pregnancy, and pregnancy rate in patients undergoing ICSI treatment.